PEMAHAMAN MAHASISWA UNIVERSITAS SILIWANGI DALAM KONSEP LITERASI LINGKUNGAN (EKOLITERASI UNTUK MEWUJUDKAN KAMPUS RAMAH LINGKUNGAN - najmuddin, alifia firdyani (Universitas Negeri Padang, 2024)
This article discusses the understanding of Geography and Biology students at Siliwangi University about ecoliteracy in creating an environmentally friendly campus. This study used a quantitative survey method with a Google Form questionnaire. The findings show that Geography students have an understanding of the concept of ecoliteracy, but 70% have difficulty implementing it, while 30% can do it. For Biology students, 60% are aware of ecoliteracy, while 40% are not. The results confirmed the influence of ecoliteracy understanding on students' awareness and actions towards the environment. This research highlights the importance of ecoliteracy in fostering concern for the environment, with an emphasis on the participation of the entire academic community, including student activity units, lecturers, and campus administrators.